Pengembangan Game Edukasi Doa Islam: Desain Arsitektur dan Implementasi - Alfian Dorif Murtadlo; Pratama Wirya Atmaja; Andreas Nugroho Sihananto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The development of educational games has become increasingly important in this modern era, particularly in addressing the challenges of engaging the younger generation in religious education. This paper presents the architectural design and implementation of an educational game focused on Islamic prayers. By leveraging technologies such as Unity for game development, Next.js for frontend web development, and Express.js for backend server functions, coupled with Supabase for efficient database management, this game offers a deep and interactive learning experience. The game's storyline encompasses various stages where players navigate scenarios related to Islamic prayers, earning rewards and knowledge along the way. Through comprehensive user analysis and iterative testing, the game aims to bridge the gap between traditional religious education and modern digital engagement. Integration of real-time performance parameters, such as call speed averaging below 30ms, ensures continuous improvement in game functionality and user experience, thereby enhancing the game's effectiveness as a learning tool. Overall, this research contributes to the advancement of educational gaming in the context of Islamic education, providing insights into effective strategies for engaging and educating young audiences in religious practices..